P41 Women's health study of Mycoplasma genitalium: a feasibility study. (23rd May 2012) - Dave, S; Kerry, S R; Oakeshott, P; McGregor, F; Cannon, E; Stephenson, J M
Abstract : Background: The role of Mycoplasma genitalium (∼3% prevalence in women) in PID is unclear. An opportunity exists to study its natural history since there are no UK treatment guidelines. We conducted a feasibility study. Objectives: In women attending GUM clinics to determine: (1) recruitment and follow-up rates after 3 and 6 months, (2) feasibility of obtaining NHS numbers, (3) facilitators and barriers to follow-up. Methods: Women aged 16–24 years recruited from two GUM clinics completed a questionnaire and provided two self-taken vaginal samples. One sample was tested for chlamydia. We are testing for M genitalium and conducting 3-month follow-up. Results: Recruitment rate was 67% (199/296). Non-responders were similar in age to responders (20.6 SD 2.5 vs 20.7 SD 2.5 years) but more likely to come from ethnic minority groups: 56% (37/66) vs 36% (71/195), p<0.05. Among responders, mean sexual debut age was 16.3 years (range 12–23 n=198); 59% (116/195) reported ≥2 sexual partners and 17% (31/186) consistently used condoms in the preceding 12 months. 8.2% (16/197) had chlamydia and 0.5% (1/197) gonorrhoea on testing. At recruitment 196 participants consented to NHS numbers being obtained and used to access medical records; 197 participants agreed to 3-month follow-up. We have been able to contact ∼50% of participants for follow-up. Discussion: Most women consented to NHS number and medical record access. This is important for investigating long-term sequelae of STIs. Fewer women took part in follow-up than agreed at recruitment. It is important to understand the reasons for this.